Character Education Values in the Garantukng Sakawokng Folk Tale: Human Obligations to God - Safrihady, Safrihady; Oktavia, Wahyuni; Havizah, Sofia Nur; Hendrasius, Hendrasius; Mardian (UIR Press, 2025)
The purpose of this study is to describe the value of character education in the Dayak Salako Garantukng Sakawokng folklore, which is related to human obligations to God. The method used is descriptive qualitative with a moral approach. The data source is a folklore told by the indigenous Dayak Salako Garantukng Sakawokng people. The research data is in the form of quotes, sentences, or paragraphs that contain character education values. Data collection techniques use the technique of listening to conversation, recording techniques, and note-taking techniques. Data collection tools include human instruments, recording devices, and data cards. Data analysis techniques include: transcription, careful reading, classification, analysis, and concluding. Data validity tests include referential adequacy, triangulation, and reader persistence/consistency. This study found 11 data of character values ​​in Dayak folklore, consisting of pious attitudes (3 data), faith and piety (3 data), gratitude (3 data), and respect for the Creator (2 data). These values ​​predominantly appear in the stories of Antu Pagayo Idup and Nek Karantiko, reflecting the strong moral and religious messages in local cultural narratives.